Answer:
We start with the equation:
(3 + 4x) + (2 -x) = 5 + 3x
Now we replace:
x = i
This is just changing all the "x"s in the equation by "i"s:
(3 + 4i) + (2 - i) = 5 + 3i
This can be viewed as 3 complex numbers:
z1 = 3 + 4i
z2 = 2 - i
z3 = 5 + 3i.
Now, let's check if equality remains true:
(3 + 4i) + (2 - i) = 5 + 3i
The first step is to use the associative and commutative properties to separate the real and imaginary parts.
(3 + 2) + (4i - i)
5 + (4 - 1)*i
5 + 3i
Then the equality remains true.
And this will be true always, for anything that we feed into the x in our initial equation:
(3 + 4x) + (2 -x) = 5 + 3x
This is because x is a variable, so it can be evaluated in any number, and the equality will still be true.